2011
DOI: 10.1093/molbev/msr293
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Functionally Diverse Alleles Associated with PTC Bitter Taste Sensitivity in Africa

Abstract: Although human bitter taste perception is hypothesized to be a dietary adaptation, little is known about genetic signatures of selection and patterns of bitter taste perception variability in ethnically diverse populations with different diets, particularly from Africa. To better understand the genetic basis and evolutionary history of bitter taste sensitivity, we sequenced a 2,975 bp region encompassing TAS2R38, a bitter taste receptor gene, in 611 Africans from 57 populations in West Central and East Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 49 publications
8
90
1
2
Order By: Relevance
“…Three polymorphisms at amino acid 49 (proline or alanine), 262 (alanine or valine), and 296 (valine or isoleucine) combine to form the taster haplotype PAV and the nontaster haplotype AVI. Other more rare haplotypes (e.g., AAV, PVI) contribute to intermediate PROP/PTC sensitivity (26,80) and are more common in African Americans than in Caucasians (30,106). The AVI and PAV haplotypes completely explain the bimodal distribution in the ability to taste PTC and up to 85% of the variability in PTC thresholds (the lowest concentration of PTC that can be distinguished from water) (36), yet these single-nucleotide polymorphisms do not completely explain the PROP phenotype (81).…”
Section: Genetics Underlying the Prop Phenotypementioning
confidence: 99%
“…Three polymorphisms at amino acid 49 (proline or alanine), 262 (alanine or valine), and 296 (valine or isoleucine) combine to form the taster haplotype PAV and the nontaster haplotype AVI. Other more rare haplotypes (e.g., AAV, PVI) contribute to intermediate PROP/PTC sensitivity (26,80) and are more common in African Americans than in Caucasians (30,106). The AVI and PAV haplotypes completely explain the bimodal distribution in the ability to taste PTC and up to 85% of the variability in PTC thresholds (the lowest concentration of PTC that can be distinguished from water) (36), yet these single-nucleotide polymorphisms do not completely explain the PROP phenotype (81).…”
Section: Genetics Underlying the Prop Phenotypementioning
confidence: 99%
“…Jahren vorhanden war, scheint besonders mit der Wahrnehmung von goitrogenen Substanzen in der Nahrung in Verbindung zu stehen (Campbell et al 2011). Träger dieser Mutation ver-…”
Section: Fettgeschmackunclassified
“…Some of the studies in this line identified genetic variants that are adaptively associated with taste perception (e.g., Campbell et al 2012), smell perception (reviewed in Hasin-Brumshtein et al 2009), skin color (e.g., Norton et al 2007), eye and hair color (e.g., Sulem et al 2007), various aspects of diet (e.g., Tishkoff et al 2007), high-altitude lifestyle (e.g., Bigham et al 2010), and immune response (reviewed in Karlsson et al 2014). These connections between genetic and phenotypic variation among healthy individuals are often considered within an adaptive framework, and more recently in the light of gene-culture coevolution (reviewed in Laland et al 2010).…”
Section: Beyond Neutral Markers In Anthropological Geneticsmentioning
confidence: 99%